Peopling a new colony: Henry Jordan, land orders, and Queensland immigration, 1861–7*. Issue 264 (22nd April 2021) - Morgan, Kenneth
Abstract: This article analyses the first years of the land order system of immigration that dominated Queensland's settlement as a colony. Queensland issued land orders worth £30 per adult to fare-paying British and Irish immigrants who were mechanics, agriculturalists and people with modest amounts of capital. This form of immigration was facilitated through the work of an Emigration Commissioner – later an Agent-General – based in the British Isles. Henry Jordan held these positions in the period 1861–6. The article argues that land orders only partly met their intended outcomes, but that Jordan's activities were essential for the scheme's limited success.